In Vitro Properties for Bioceramics Composed of Silica and Titanium Oxide Composites - I-Hao Chen; Meng-Jia Lian; Wei Fang; Bo-Rui Huang; Tzu-Hao Liu; Jhih-An Chen; Chih-Ling Huang; Tzer-Min Lee (Applied Sciences, 2018)
It is important for oral and maxillofacial surgeons to repair craniofacial defects on oral cancer patients or patients with congenital problems. Thus, it is a challenge to develop biomaterials that promote bone regeneration as potential materials for bone repair. This work is devoted to the fabrication of bioceramics composed of silica and titanium oxide with various concentrations of titanium oxide for developing bone repair materials for dentistry and tissue engineering. The silica-based bioceramics were synthesized using the sol–gel method, and titanium oxide was added from the hydrolysis of tetrabutyl titanate. The surface morphology was observed using scanning electron microscopy. The chemical composition was measured using an energy dispersive X-ray spectrometer, and the crystal structure was identified by using an X-ray diffraction diffractometer. The pH value and ion concentrations released in simulated body fluids after immersion with bioceramic samples were measured using a pH meter and inductively coupled plasma mass spectrometry, respectively. In the cell toxicity test, the human osteosarcoma cells (MG63) were used and quantitatively assessed using an MTT assay. The results showed that the proposed bioceramics can be controlled by tuning the Si/Ti ratio to modify the dissolution rate of samples and enhance the formation of apatite. Compared to Dulbecco’s modified Eagle’s medium (DMEM) groups, the cell number of the BG_Ti75 group can be increased to 120%. Furthermore, BG_Ti75 can promote MG63 cell growth with statistical significance and keep the pH value and the released calcium ion concentrations of the soaking environment stable. The proposed bioceramics show potential for bone-regenerating capability.